SAFETY CULTURE OF APPROVED TRAINING ORGANIZATIONS: BASIS FOR AN EMERGENCY RESPONSE PLAN MANUAL - B. Abari, Jeric; Oliver F. Cortez, Richard; A. Sario, Jay (Penerbit Lafadz Jaya, 2024)
Every Approved Training Organization (ATO) follows the safety standards imposed by the Civil Aviation Authority of the Philippines (CAAP). As per the FAA (2023), safety culture is essential to the effectiveness of safety performance, and it will inevitably be a requisite to the general output of the organization. However, in the Philippines, there is little to no studies relating to such topic. The paper aims to find out the level of engagement and implementation of the Approved Training Organization in the Philippines (ATO). Moreover, to look into the relationship of the ATOs Safety Management System process engagement and implementation towards safety motivation, safety compliance, safety participation, and safety reporting behavior. Lastly, to find out the differences and also the variations in safety culture perception. It made use of a concurrent-embedded mixed method approach, in which the researcher presents both quantitative and qualitative data collected. In summary of the findings, there is a positive agreement resulting to a positive practice of safety culture within the surveyed aviation schools, with a strong commitment to safety policies, reporting, compliance, and participation. While, the high R-squared values for Safety Reporting Behavior and Safety Participation signified strong model fits. These results imply that the model effectively shows the difference in safety-related behaviors and participation, highlighting its reliability. Moreover, there is no significant differences in perceptions among demographic variables as to gender and functional group for safety reporting behavior, safety compliance, and safety participation across all three aviation schools. The variations or differences in perceptions among demographic variables were generally not significant, signifying a consistent safety culture regardless of gender or functional position. With the results of the study, it served as a basis in proposing a SMS policy implementation for the selected aviation schools in the Philippines.